Heroísmo y suerte en hija de la fortuna : análisis de las parejas actanciales - Onguedou, Georges Moukouti (Acta Hispanica, 2010)
Isabel Allende’s Hija de la fortuna (1999) relates the itinerary of the young ElizaSommers from Valparaíso (Chile) to California (United States) by the middle of the XIXCentury. The trip, caused by the Gold Rush, is also undertaken by other Hispanics. Thisevent supposes the possibilities of attraction and repulsion of the Californian space. In afunctional analysis of the couples of actors, it’s possible to see the different forces in the heroicaction of the main character. It can also be noticed how some particular forces – spaces andcharacters mainly – interact.